Comparative microfluidic screening of amino acid salt solutions for post-combustion CO2 capture. (December 2015) - Hallenbeck, Alexander P.; Egbebi, Adefemi; Resnik, Kevin P.; Hopkinson, David; Anna, Shelley L.; Kitchin, John R.
Abstract : Highlights: We measure the CO2 absorption capacity of amino acid salts in a microfluidic device. CO2 loading of absorbent solutions can be measured with <1 mL of sample in <1 h. CO2 loadings measured with microfluidic device are compared with CSTR measurements. Salt of lysine absorbed >90% more CO2 on a per mole of amine/amino acid basis than MEA. Raman spectroscopy was used to determine reaction products for each amino acid salt. Abstract: The CO2 absorption capacity and rate of aqueous solutions of MEA and the potassium salts of glycine, taurine, proline, and lysine were compared in a microfluidic device. These properties were measured by tracking the volume change of an entrained CO2 gas plug as it traveled through a microfluidic channel. The potassium salt of lysine, which contains two primary amine functional groups, exhibited the highest rich CO2 loading, >50% higher than MEA. The salts of glycine, and taurine exhibited similar absorption capacity to MEA, and the salt of proline exhibited the lowest absorption capacity. The trend in absorption capacities of the potassium salt of lysine and MEA was also observed in a set of breakthrough CSTR experiments. Raman spectroscopy was used to analyze the absorbent solutions before exposure to CO2 as well as the reactor effluent. Spectral features of carbamate, carbonate, and bicarbonate were identified in the effluent spectra. The effectiveness of the microfluidic reactor as a solvent volume and time efficient screening tool is demonstrated. The results suggest further work should be done to evaluate the efficacy of the alkali salt of lysine as a post-combustion CO2 capture absorbent as it has potential to match or possibly improve upon the CO2 loading of MEA while offering advantages such as low toxicity and lower volatility.